ALK -rearranged Mesenchymal Neoplasms With Prominent Foamy/Pseudolipogenic Cell Morphology : Expanding the Phenotypic Spectrum of ALK Fusion Neoplasms and Report of Novel Fusion Partners. - Agaimy, Abbas; Stöhr, Robert; Fisher, Cyril; Chrisinger, John S.A.; Demicco, Elizabeth G.; Tögel, Lars; Michal, Michal; Michal, Michael (American Journal of Surgical Pathology, 2024)
The category of ALK -rearranged mesenchymal neoplasms has been evolving rapidly, with reports of morphologically diverse lesions of cutaneous, soft tissue, and visceral origin. While some of these represent morphologically defined entities harboring recurrent ALK fusions (inflammatory myofibroblastic tumor and epithelioid fibrous histiocytoma), others are unclassified by morphology with variable overlap with the tyrosine kinase family of neoplasia and their underlying ALK fusions cannot be suspected based on morphology. We herein report 3 cases that expand the anatomic, morphologic, and genotypic spectrum of ALK -rearranged unclassified neoplasms. Patients were all adults aged 46 to 69 (median: 63) who presented with a mass located in the gingiva, subcutis of the back, and submucosal posterior pharyngeal wall. The tumor size ranged from 1 to 2.7 cm (median: 1.6). Conservative surgery was the treatment in all patients. Follow-up was available for one patient who remained disease-free at 14 months. Histologically, all tumors displayed large polygonal cells with foamy to granular and lipogenic-like microvacuolated copious cytoplasm and medium-sized round nuclei with 1 or 2 prominent nucleoli. Mitoses and necrosis were not seen. The initial diagnostic impression was PEComa, inflammatory rhabdomyoblastic tumor and unclassified pseudolipogenic neoplasm. Strong cytoplasmic ALK was detected by immunohistochemistry in all cases. Other positive markers include Cathepsin K (2/2), desmin (1/3), focal MyoD1 (1/1), focal SMA (1/3), and focal EMA (1/2). Targeted RNA sequencing revealed ALK fusions with exon 20 (2 cases) and exon 19 (one case) of ALK fused to RND3 (exon 3), SQSTM1 (exon 6), and desmin (intron 6). Methylation profiling in the desmin-fused case (initially diagnosed as inflammatory rhabdomyoblastic tumor) revealed an inflammatory myofibroblastic tumor match with a low confidence score of 0.5 and a flat copy number variation (CNV) profile. No NF1 mutation was detected in this case, altogether excluding an inflammatory rhabdomyoblastic tumor. Our study highlights and expands the morphologic and anatomic diversity of ALK- fused neoplasms and documents novel fusion partners ( RND3 and desmin).
EVALuna2:570327

Benchmarking whole exome sequencing in the German network for personalized medicine - Menzel, Michael; Martis-Thiele, Mihaela; Goldschmid, Hannah; Ott, Alexander; Romanovsky, Eva; Siemanowski-Hrach, Janna; Seillier, Lancelot; Brüchle, Nadina Ortiz; Maurer, Angela; Lehmann, Kjong Van; Begemann, Matthias; Elbracht, Miriam; et al. (European Journal of Cancer, 2024)
Introduction: Whole Exome Sequencing (WES) has emerged as an efficient tool in clinical cancer diagnostics to broaden the scope from panel-based diagnostics to screening of all genes and enabling robust determination of complex biomarkers in a single analysis. Methods: To assess concordance, six formalin-fixed paraffin-embedded (FFPE) tissue specimens and four commercial reference standards were analyzed by WES as matched tumor-normal DNA at 21 NGS centers in Germany, each employing local wet-lab and bioinformatics. Somatic and germline variants, copy-number alterations (CNAs), and complex biomarkers were investigated. Somatic variant calling was performed in 494 diagnostically relevant cancer genes. The raw data were collected and re-analyzed with a central bioinformatic pipeline to separate wet- and dry-lab variability. Results: The mean positive percentage agreement (PPA) of somatic variant calling was 76 % while the positive predictive value (PPV) was 89 % in relation to a consensus list of variants found by at least five centers. Variant filtering was identified as the main cause for divergent variant calls. Adjusting filter criteria and re-analysis increased the PPA to 88 % for all and 97 % for the clinically relevant variants. CNA calls were concordant for 82 % of genomic regions. Homologous recombination deficiency (HRD), tumor mutational burden (TMB), and microsatellite instability (MSI) status were concordant for 94 %, 93 %, and 93 % of calls, respectively. Variability of CNAs and complex biomarkers did not decrease considerably after harmonization of the bioinformatic processing and was hence attributed mainly to wet-lab differences. Conclusion: Continuous optimization of bioinformatic workflows and participating in round robin tests are recommended.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Clinical exome; Molecular pathology; Multi-centric inter-laboratory test; Precision oncology; Whole exome sequencing

Comparative analysis of tumour mutational burden (TMB) prediction methods and its association with determinants of the tumour immune microenvironment of urothelial bladder cancer (UBC) - Eckstein, Markus; Hartmann, Arndt; Strissel, Pamela; Strick, Reiner; Wach, S.; Taubert, Helge; Wullich, Bernd; Geppert, Carol-Immanuel; Weyerer, Veronika; Stöhr, Robert; Rübner, Matthias; Fasching, Peter; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Determinants Affecting the Clinical Implementation of a Molecularly Informed Molecular Tumor Board Recommendation: Experience from a Tertiary Cancer Center. - Tögel, Lars; Schubart, Christoph; Lettmaier, Sebastian; Neufert, Clemens; Hoyer, Juliane; Wolff, Kerstin; Moskalev, Evgeny; Stöhr, Robert; Agaimy, Abbas; Wiesmann da Silva Reis, André; Wullich, Bernd; Mackensen, Andreas; et al. (Cancers, 2023)
Molecular Tumor Boards (MTBs) converge state-of-the-art next-generation sequencing (NGS) methods with the expertise of an interdisciplinary team consisting of clinicians, pathologists, human geneticists, and molecular biologists to provide molecularly informed guidance in clinical decision making to the treating physician. In the present study, we particularly focused on elucidating the factors impacting on the clinical translation of MTB recommendations, utilizing data generated from gene panel mediated comprehensive genomic profiling (CGP) of 554 patients at the MTB of the Comprehensive Cancer Center Erlangen, Germany, during the years 2016 to 2020. A subgroup analysis of cases with available follow-up data (n = 332) revealed 139 cases with a molecularly informed MTB recommendation, which was successfully implemented in the clinic in 44 (31.7%) of these cases. Here, the molecularly matched treatment was applied in 45.4% (n = 20/44) of cases for ≥6 months and in 25% (n = 11/44) of cases for 12 months or longer (median time to treatment failure, TTF: 5 months, min: 1 month, max: 38 months, ongoing at data cut-off). In general, recommendations were preferentially implemented in the clinic when of high (i.e., tier 1) clinical evidence level. In particular, this was the case for MTB recommendations suggesting the application of PARP, PIK3CA, and IDH1/2 inhibitors. The main reason for non-compliance to the MTB recommendation was either the application of non-matched treatment modalities (n = 30)/stable disease (n = 7), or deteriorating patient condition (n = 22)/death of patient (n = 9). In summary, this study provides an insight into the factors affecting the clinical implementation of molecularly informed MTB recommendations, and careful considerations of these factors may guide future processes of clinical decision making.
EVALuna2:545872
Keywords: Molecular Tumor Board; clinical decision making; precision medicine; molecular pathology; real-world data; cancer care

ERBB2/ ERBB3-mutated S100/ SOX10-positive unclassified high-grade uterine sarcoma: first detailed description of a novel entity - Agaimy, Abbas; Dermawan, Josephine K.; Haller, Florian; Semrau, Sabine; Meidenbauer, Norbert; Stöhr, Robert; Lax, Sigurd; Hartmann, Arndt; Zou, Ying S.; Xing, Deyin; Tögel, Lars; Gross, John M.; et al. (Virchows Archiv, 2024)
With the increasing use of innovative next generation sequencing (NGS) platforms in routine diagnostic and research settings, the genetic landscape of uterine sarcomas has been dynamically evolving during the last two decades. Notably, the majority of recently recognized genotypes in uterine sarcomas represent gene fusions, while recurrent oncogene mutations of diagnostic and/ or therapeutic value have been rare. Recently, a distinctive aggressive uterine sarcoma expressing S100 and SOX10, but otherwise lacking diagnostic morphological, immunophenotypic and molecular features of other uterine malignancies has been presented in a scientific abstract form (USCAP, 2023), but detailed description and delineation of the entity is still missing. We herein describe two high-grade unclassified uterine sarcomas characterized by spindle to round cell morphology and diffuse expression of S100 and SOX10, originating in the uterine body and cervix of 53- and 45-year-old women and carrying an ERBB3 (p.Glu928Gly) and an ERBB2 (p.Val777Leu) mutation, respectively. Both tumors harbored in addition genomic HER2 amplification, ATRX mutation and CDKN2A deletion. Methylation studies revealed a methylome most similar to MPNST-like tumors, but distinct from melanoma, MPNST, clear cell sarcoma, and endometrial stromal sarcoma. Case 1 died of progressive peritoneal metastases after multiple trials of chemotherapy 47 months after diagnosis. Case 2 is a recent case who presented with a cervical mass, which was biopsied. This study defines a novel heretofore unrecognized aggressive uterine sarcoma with unique phenotypic and genotypic features. Given the potential value of targeting HER2, recognizing this tumor type is mandatory for appropriate therapeutic strategies and for better future delineation of the entity.
CRIS-Team Scopus Importer:2024-09-06
Keywords: EGFR; Molecular profiling; nerve sheath tumor; Targeted therapy; Tyrosine kinase fusions; Undifferentiated uterine sarcoma

Gene fusions are frequent in ACTH-secreting neuroendocrine neoplasms of the pancreas, but not in their non-pancreatic counterparts - Agaimy, Abbas; Kasajima, Atsuko; Stöhr, Robert; Haller, Florian; Schubart, Christoph; Tögel, Lars; Pfarr, Nicole; von Werder, Alexander; Pavel, Marianne Ellen; Sessa, Fausto; Uccella, Silvia; La Rosa, Stefano; et al. (Virchows Archiv, 2023)
Ectopic Cushing syndrome is a rare clinical disorder resulting from excessive adrenocorticotrophic hormone (ACTH) produced by non-pituitary neoplasms, mainly neuroendocrine neoplasms (NENs) of the lung, pancreas, and gastrointestinal tract, and other less common sites. The genetic background of ACTH-producing NENs has not been well studied. Inspired by an index case of ACTH-producing pancreatic NEN carrying a gene fusion, we postulated that ACTH-producing NENs might be enriched for gene fusions. We herein examined 21 ACTH-secreting NENs of the pancreas (10), lung (9), thymus (1), and kidney (1) using targeted RNA sequencing. The tumors were classified according to the most recent WHO classification as NET-G1/typical carcinoid (n = 4), NETG-2/atypical carcinoid (n = 14), and NET-G3 (n = 3). Overall, targeted RNA sequencing was successful in 11 cases (4 of 10 pancreatic tumors, 5 of 9 pulmonary tumors, and in the one renal and one thymic tumor). All four successfully tested pancreatic tumors revealed a gene fusion: two had a EWSR1::BEND2 and one case each had a KMT2A::BCOR and a TFG::ADGRG7 fusion, respectively. EWSR1 rearrangements were confirmed in both tumors with a EWSR1::BEND2 by FISH. Gene fusions were mutually exclusive with ATRX, DAXX, and MEN1 mutations (the most frequently mutated genes in NETs) in all four cases. Using RNA-based variant assessment (n = 16) or via the TSO500 panel (n = 5), no pathogenic BCOR mutations were detected in any of the cases. Taken together, gene fusions were detected in 4/4 (100%) pancreatic versus 0/7 (0%) non-pancreatic tumors, respectively. These results suggest a potential role for gene fusions in triggering the ACTH production in pancreatic NENs presenting with ectopic Cushing syndrome. While the exact mechanisms responsible for the ectopic ACTH secretion are beyond the scope of this study, overexpressed fusion proteins might be involved in promoter-mediated overexpression of pre-ACTH precursors in analogy to the mechanisms postulated for EWSR1::CREB1-mediated paraneoplastic phenomena in certain mesenchymal neoplasms. The genetic background of the ACTH-producing non-pancreatic NENs remains to be further studied.
CRIS-Team Scopus Importer:2023-02-03
Keywords: ACTH; Neuroendocrine tumor; NET; ectopic Cushing; EWSR1; BCOR fusion; BEND2 fusion; KMT2A

Harmonization and Standardization of Panel-Based Tumor Mutational Burden Measurement: Real-World Results and Recommendations of the Quality in Pathology Study - Stenzinger, Albrecht; Endris, Volker; Budczies, Jan; Merkelbach-Bruse, Sabine; Kazdal, Daniel; Dietmaier, Wolfgang; Pfarr, Nicole; Siebolts, Udo; Hummel, Michael; Herold, Sylvia; Andreas, Johanna; Zoche, Martin; et al. (Journal of Thoracic Oncology, 2020)
Introduction: Tumor mutational burden (TMB) is a quantitative assessment of the number of somatic mutations within a tumor genome. Immunotherapy benefit has been associated with TMB assessed by whole-exome sequencing (wesTMB) and gene panel sequencing (psTMB). The initiatives of Quality in Pathology (QuIP) and Friends of Cancer Research have jointly addressed the need for harmonization among TMB testing options in tissues. This QuIP study identifies critical sources of variation in psTMB assessment. Methods: A total of 20 samples from three tumor types (lung adenocarcinoma, head and neck squamous cell carcinoma, and colon adenocarcinoma) with available WES data were analyzed for psTMB using six panels across 15 testing centers. Interlaboratory and interplatform variation, including agreement on variant calling and TMB classification, were investigated. Bridging factors to transform psTMB to wesTMB values were empirically derived. The impact of germline filtering was evaluated. Results: Sixteen samples had low interlaboratory and interpanel psTMB variation, with 87.7% of pairwise comparisons revealing a Spearman's ρ greater than 0.6. A wesTMB cut point of 199 missense mutations projected to psTMB cut points between 7.8 and 12.6 mutations per megabase pair; the corresponding psTMB and wesTMB classifications agreed in 74.9% of cases. For three-tier classification with cut points of 100 and 300 mutations, agreement was observed in 76.7%, weak misclassification in 21.8%, and strong misclassification in 1.5% of cases. Confounders of psTMB estimation included fixation artifacts, DNA input, sequencing depth, genome coverage, and variant allele frequency cut points. Conclusions: This study provides real-world evidence that all evaluated panels can be used to estimate TMB in a routine diagnostic setting and identifies important parameters for reliable tissue TMB assessment that require careful control. As complex or composite biomarkers beyond TMB are likely playing an increasing role in therapy prediction, the efforts by QuIP and Friends of Cancer Research also delineate a general framework and blueprint for the evaluation of such assays.
CRIS-Team Scopus Importer:2020-04-24
Keywords: Gene panel; Immuno-oncology; Lung cancer; Quality assurance; Sequencing; TMB; Tumor mutational burden

Identification of Disparities in Personalized Cancer Care—A Joint Approach of the German WERA Consortium - Lüke, Florian; Haller, Florian; Utpatel, Kirsten; Krebs, Markus; Meidenbauer, Norbert; Scheiter, Alexander; Spörl, Silvia; Heudobler, Daniel; Sparrer, Daniela; Kaiser, Ulrich; Keil, Felix; Schubart, Christoph; et al. (Cancers, 2022)
(1) Background: molecular tumor boards (MTBs) are crucial instruments for discussing and allocating targeted therapies to suitable cancer patients based on genetic findings. Currently, limited evidence is available regarding the regional impact and the outreach component of MTBs; (2) Methods: we analyzed MTB patient data from four neighboring Bavarian tertiary care oncology centers in Würzburg, Erlangen, Regensburg, and Augsburg, together constituting the WERA Alliance. Absolute patient numbers and regional distribution across the WERA-wide catchment area were weighted with local population densities; (3) Results: the highest MTB patient numbers were found close to the four cancer centers. However, peaks in absolute patient numbers were also detected in more distant and rural areas. Moreover, weighting absolute numbers with local population density allowed for identifying so-called white spots—regions within our catchment that were relatively underrepresented in WERA MTBs; (4) Conclusions: investigating patient data from four neighboring cancer centers, we comprehensively assessed the regional impact of our MTBs. The results confirmed the success of existing collaborative structures with our regional partners. Additionally, our results help identifying potential white spots in providing precision oncology and help establishing a joint WERA-wide outreach strategy.
CRIS-Team Scopus Importer:2022-11-04
Keywords: cancer care; MTB; outcomes research; outreach; patient access; precision oncology; real world data

Integrating Genomics and Clinical Data for Statistical Analysis by Using GEnome MINIng (GEMINI) and Fast Healthcare Interoperability Resources (FHIR): System Design and Implementation - Gründner, Julian; Wolf, Nicolas; Tögel, Lars; Haller, Florian; Prokosch, Hans-Ulrich; Christoph, Jan (Journal of Medical Internet Research, 2020)
Background: The introduction of next-generation sequencing (NGS) into molecular cancer diagnostics has led to an increase in the data available for the identification and evaluation of driver mutations and for defining personalized cancer treatment regimens. The meaningful combination of omics data, ie, pathogenic gene variants and alterations with other patient data, to understand the full picture of malignancy has been challenging.
CRIS-Team WoS Importer:2020-12-11

Met amplification in non‐small cell lung cancer (Nsclc)— a consecutive evaluation using next‐generation sequencing (ngs) in a real‐world setting - Schubart, Christoph; Stöhr, Robert; Tögel, Lars; Fuchs, Florian; Sirbu, Horia; Seitz, Gerhard; Seggewiss‐bernhardt, Ruth; Leistner, Rumo; Sterlacci, William; Seidl, Christoph; Mugler, Michael; Kapp, Markus; et al. (Cancers, 2021)
In non‐small cell lung cancer (NSCLC), approximately 1–3% of cases harbor an increased gene copy number (GCN) of the MET gene. This alteration can be due to de novo amplification of the MET gene or can represent a secondary resistance mechanism in response to targeted therapies. To date, the gold standard method to evaluate the GCN of MET is fluorescence in situ hybridization (FISH). However, next‐generation sequencing (NGS) is becoming more relevant to optimize therapy by revealing the mutational profile of each NSCLC. Using evaluable n = 205 NSCLC cases of a consecutive cohort, this study addressed the question of whether an amplicon based NGS assay can completely replace the FISH method regarding the classification of MET GCN status. Out of the 205 evaluable cases, only n = 9 cases (43.7%) of n = 16 high‐level MET amplified cases assessed by FISH were classified as amplified by NGS. Cases harboring a MET GCN >10 showed the best concordance when comparing FISH versus NGS (80%). This study confirms that an amplicon‐based NGS assessment of the MET GCN detects high‐level MET amplified cases harboring a MET GCN >10 but fails to detect the various facets of MET gene amplification in the context of a therapy‐induced resistance mechanism.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Amplification; Fluorescence in situ hybridization; MET; MET inhibitor; Next‐generation sequencing; NSCLC; Precision medicine; Resistance mechanism

NSD3-NUTM1-rearranged carcinoma of the median neck/thyroid bed developing after recent thyroidectomy for sclerosing mucoepidermoid carcinoma with eosinophilia: report of an extraordinary case - Agaimy, Abbas; Tögel, Lars; Stöhr, Robert; Meidenbauer, Norbert; Semrau, Sabine; Hartmann, Arndt; Mantsopoulos, Konstantinos (Virchows Archiv, 2021)
Sclerosing mucoepidermoid carcinoma with eosinophilia (SMECE) is an exceedingly rare low-grade thyroid malignancy of unknown histogenesis. NUT carcinoma is another rare, highly aggressive neoplasm with predilection for the midline, defined by recurrent NUTM1 fusions. The bromodomain family genes (BRD4 or BRD3) and rarely NSD3, ZNF532, or others are known fusion partners. We describe an extraordinary case of a 42-year-old female with a thyroid SMECE treated by thyroidectomy and neck dissection. She presented 6 months later with extensive midline recurrence encasing/compressing the trachea. Biopsy revealed poorly differentiated carcinoma with abrupt squamous differentiation, suggestive of NUT carcinoma. Immunohistochemistry confirmed expression of monoclonal NUT antibody. Targeted RNA sequencing revealed the NSD3-NUTM1 fusion in the NUT carcinoma, but not in the SMECE. This unique case highlights unusual sequential origin of two exceptionally rare entities at same anatomic site and underlines the necessity of sampling unexpectedly aggressive recurrences of otherwise indolent malignancies.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Head and neck; Midline carcinoma; NSD3; NUT carcinoma; NUTM1; Sclerosing mucoepidermoid carcinoma with eosinophilia; Thyroid gland

Recording of the regional Origin Areas of Patients from the Molecular Tumor Board to Identify the "white Spots" in the Service Area - A joint Initiative of the Bavarian CCC WERA Alliance - Lueke, F.; Haller, F.; Utpatel, K.; Krebs, M.; Meidenbauer, Norbert; Scheiter, A.; Spörl, Silvia; Heudobler, D.; Keil, F.; Schubart, Christoph; Tögel, Lars; Einhell, S.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Response to treatment of uncommon EGFR mutations - a retrospective analysis from the German National Network Genomic Medicine Lung Cancer (nNGM) - Janning, M.; Sueptitz, J.; Forstreuter, A.; Albers-Leischner, C.; Tufman, A.; Velthaus-Rusik, J. -L; Reck, M.; Jung, A.; Kauffmann-Guerrero, D.; Bonzheim, I.; Braendlein, S.; Hummel, H.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Successful targeting of BRAF V600E mutation with vemurafenib in a treatment-resistant extragonadal non-seminomatous germ cell tumor - Meintker, Lisa; Haller, Florian; Tögel, Lars; Schmidt, Daniela; Waibel, Heidi; Mackensen, Andreas; Meidenbauer, Norbert (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Successful Targeting of BRAF V600E Mutation With Vemurafenib in a Treatment-Resistant Extragonadal Nonseminomatous Germ-Cell Tumor - Meintker, Lisa; Haller, Florian; Tögel, Lars; Schmidt, Daniela; Waibel, Heidi; Hartmann, Arndt; Mackensen, Andreas; Meidenbauer, Norbert (JCO Precision Oncology, 2020)

Tert promoter mutation analysis of whole-organ mapping bladder cancers - Weyerer, Veronika; Eckstein, Markus; Strissel, Pamela; Wullweber, Adrian; Lange, Fabienne; Tögel, Lars; Geppert, Carol-Immanuel; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Hartmann, Arndt; et al. (Genes, 2021)
Background: Multifocal occurrence is a main characteristic of urothelial bladder cancer (UBC). Whether urothelial transformation is caused by monoclonal events within the urothelium, or by polyclonal unrelated events resulting in several tumor clones is still under debate. TERT promoter mutations are the most common somatic alteration identified in UBC. In this study, we analyzed different histological tissues from whole-organ mapping bladder cancer specimens to reveal TERT mutational status, as well as to discern how tumors develop. Methods: Up to 23 tissues from nine whole-organ mapping bladder tumor specimens, were tested for TERT promoter mutations including tumor associated normal urothelium, non-invasive urothelial lesions (hyperplasia, dys-plasia, metaplasia), carcinoma in situ (CIS) and different areas of muscle invasive bladder cancers (MIBC). The mutational DNA hotspot region within the TERT promoter was analyzed by SNaPshot analysis including three hot spot regions (−57, −124 or −146). Telomere length was measured by the Relative Human Telomere Length Quantification qPCR Assay Kit. Results: TERT promoter mutations were identified in tumor associated normal urothelium as well as non-invasive urothelial lesions, CIS and MIBC. Analysis of separate regions of the MIBC showed 100% concordance of TERT promoter mutations within a respective whole-organ bladder specimen. Polyclonal events were observed in five out of nine whole-organ mapping bladder cancers housing tumor associated normal urothelium, non-invasive urothelial lesions and CIS where different TERT promoter mutations were found compared to MIBC. The remaining four whole-organ mapping bladders were monoclonal for TERT mutations. No significant differences of telomere length were observed. Conclusions: Examining multiple whole-organ mapping bladders we conclude that TERT promoter mutations may be an early step in bladder cancer carcinogenesis as supported by TERT mutations detected in tumor associated normal urothelium as well as non-invasive urothelial lesions. Since mutated TERT promoter regions within non-invasive urothelial lesions are not sufficient alone for the establishment of cancerous growth, this points to the contribution of other gene mutations as a requirement for tumor development.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Clonality; TERT promoter mutation; Whole-organ mapping bladder tumor

TFE3 -rearranged Head and Neck Neoplasms : Twenty-two Cases Spanning the Morphologic Continuum Between Alveolar Soft Part Sarcoma and PEComa and Highlighting Genotypic Diversity. - Agaimy, Abbas; Michal, Michael; Abdelsatir, Ali; Abdelsatir, Azza A.; Abdulrahim, Sawsan; Laco, Jan; Ihrler, Stephan; Tögel, Lars; Stöhr, Robert; Bishop, Justin A.; Din, Nasir Ud; Michal, Michal (American Journal of Surgical Pathology, 2025)
TFE3 rearrangements characterize histogenetically, topographically, and biologically diverse neoplasms. Besides being a universal defining feature in alveolar soft part sarcoma (ASPS) and clear cell stromal tumor of the lung, TFE3 fusions have been reported in subsets of renal cell carcinoma, perivascular epithelioid cell tumor (PEComa), epithelioid hemangioendothelioma and ossifying fibromyxoid tumors. TFE3 -related neoplasms are rare in the head and neck and may pose diagnostic challenges. We herein describe 22 TFE3 fusion neoplasms affecting 11 males and 11 females aged 4 to 79 years (median, 25) and involving different head and neck sites: sinonasal cavities (n = 8), tongue (n = 4), oral cavity/oropharynx (n = 3), salivary glands (n = 2), orbit (n = 2), and soft tissue or unspecified sites (n = 3). Based on morphology and myomelanocytic immunophenotype, 10 tumors qualified as ASPS, 7 as PEComas (3 melanotic; all sinonasal), and 5 showed intermediate (indeterminate) histology overlapping with ASPS and PEComa. Immunohistochemistry for TFE3 was homogeneously strongly positive in all cases. Targeted RNA sequencing/FISH testing confirmed TFE3 fusions in 14 of 16 successfully tested cases (88%). ASPSCR1 was the most frequent fusion partner in ASPS (4 of 5 cases); one ASPS had a rare VCP::TFE3 fusion. The 6 successfully tested PEComas had known fusion partners as reported in renal cell carcinoma and PEComas ( NONO, PRCC, SFPQ , and PSPC1 ). The indeterminate tumors harbored ASPSCR1::TFE3 (n = 2) and U2AF2::TFE3 (n = 1) fusions, respectively. This large series devoted to TFE3-positive head and neck tumors illustrates the recently proposed morphologic overlap in the spectrum of TFE3 -associated mesenchymal neoplasms. While all PEComas were sinonasal, ASPS was never sinonasal and occurred in diverse head and neck sites with a predilection for the tongue. The indeterminate (PEComa-like) category is molecularly more akin to ASPS but shows different age, sex, and anatomic distribution compared with classic ASPS. We report VCP as a novel fusion partner in ASPS and PSPC1 as a novel TFE3 fusion partner in PEComa (detected in one PEComa). Future studies should shed light on the most appropriate terminological subtyping of these highly overlapping tumors.
EVALuna2:578182

The WERA cancer center matrix: Strategic management of patient access to precision oncology in a large and mostly rural area of Germany - Krebs, Markus; Haller, Florian; Spörl, Silvia; Gerhard-Hartmann, Elena; Utpatel, Kirsten; Maurus, Katja; Kunzmann, Volker; Chatterjee, Manik; Venkataramani, Vivek; Maatouk, Imad; Bittrich, Max; Einwag, Tatjana; et al. (European Journal of Cancer, 2024)
Purpose: Providing patient access to precision oncology (PO) is a major challenge of clinical oncologists. Here, we provide an easily transferable model from strategic management science to assess the outreach of a cancer center. Methods: As members of the German WERA alliance, the cancer centers in Würzburg, Erlangen, Regensburg and Augsburg merged care data regarding their geographical impact. Specifically, we examined the provenance of patients from WERA´s molecular tumor boards (MTBs) between 2020 and 2022 (n = 2243). As second dimension, we added the provenance of patients receiving general cancer care by WERA. Clustering our catchment area along these two dimensions set up a four-quadrant matrix consisting of postal code areas with referrals towards WERA. These areas were re-identified on a map of the Federal State of Bavaria. Results: The WERA matrix overlooked an active screening area of 821 postal code areas – representing about 50 % of Bavaria´s spatial expansion and more than six million inhabitants. The WERA matrix identified regions successfully connected to our outreach structures in terms of subsidiarity – with general cancer care mainly performed locally but PO performed in collaboration with WERA. We also detected postal code areas with a potential PO backlog – characterized by high levels of cancer care performed by WERA and low levels or no MTB representation. Conclusions: The WERA matrix provided a transparent portfolio of postal code areas, which helped assessing the geographical impact of our PO program. We believe that its intuitive principle can easily be transferred to other cancer centers.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Cancer care facilities; Community health services; Health services administration; Healthcare disparities; Intersectoral collaboration; Tertiary healthcare

Treatment outcome of atypical EGFR mutations in the German National Network Genomic Medicine Lung Cancer (nNGM) - Janning, M.; Süptitz, J.; Albers-Leischner, C.; Delpy, P.; Tufman, A.; Velthaus-Rusik, J. L.; Reck, M.; Jung, A.; Kauffmann-Guerrero, D.; Bonzheim, I.; Brändlein, S.; Hummel, H. D.; et al. (Annals of Oncology, 2022)
Background: Atypical EGFR mutations occur in 10%-30% of non-small-cell lung cancer (NSCLC) patients with EGFR mutations and their sensitivity to classical epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKI) is highly heterogeneous. Patients harboring one group of uncommon, recurrent EGFR mutations (G719X, S768I, L861Q) respond to EGFR-TKI. Exon 20 insertions are mostly insensitive to EGFR-TKI but display sensitivity to exon 20 inhibitors. Clinical outcome data of patients with very rare point and compound mutations upon systemic treatments are still sparse to date. Patients and methods: In this retrospective, multicenter study of the national Network Genomic Medicine (nNGM) in Germany, 856 NSCLC cases with atypical EGFR mutations including co-occurring mutations were reported from 12 centers. Clinical follow-up data after treatment with different EGFR-TKIs, chemotherapy and immune checkpoint inhibitors were available from 260 patients. Response to treatment was analyzed in three major groups: (i) uncommon mutations (G719X, S7681, L861Q and combinations), (ii) exon 20 insertions and (iii) very rare EGFR mutations (very rare single point mutations, compound mutations, exon 18 deletions, exon 19 insertions). Results: Our study comprises the largest thus far reported real-world cohort of very rare EGFR single point and compound mutations treated with different systemic treatments. We validated higher efficacy of EGFR-TKI in comparison to chemotherapy in group 1 (uncommon), while most exon 20 insertions (group 2) were not EGFR-TKI responsive. In addition, we found TKI sensitivity of very rare point mutations (group 3) and of complex EGFR mutations containing exon 19 deletions or L858R mutations independent of the combination partner. Notably, treatment responses in group 3 (very rare) were highly heterogeneous. Co-occurring TP53 mutations exerted a non-significant trend for a detrimental effect on outcome in EGFR-TKI-treated patients in groups 2 and 3 but not in group 1. Conclusions: Based on our findings, we propose a novel nNGM classification of atypical EGFR mutations.
CRIS-Team Scopus Importer:2022-05-20
Keywords: atypical EGFR mutations; EGFR; non-small-cell lung cancer

Use of NGS Gene Panel Analyzes for molecularly targeted System Therapy - Roesch, Johannes; Haller, Florian; Lettmaier, Sebastian; Haderlein, Marlen; Hartmann, Arndt; Moskalev, Evgeny; Tögel, Lars; Putz, Florian; Weissmann, T.; Schubert, P.; Höfler, Daniel; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

YAP1-MAML2-Rearranged Poroid Squamous Cell Carcinoma (Squamoid Porocarcinoma) Presenting as a Primary Parotid Gland Tumor - Agaimy, Abbas; Stöhr, Robert; Tögel, Lars; Hartmann, Arndt; Cramer, Thomas (Head and Neck Pathology, 2020)
Porocarcinoma (synonym: malignant eccrine poroma) is a rare aggressive carcinoma type with terminal sweat gland duct differentiation. The squamous variant of porocarcinoma is even less frequent and might be indistinguishable from conventional squamous cell carcinoma (SCC). We herein describe the first case of a carcinoma presenting as a primary parotid gland malignancy in a 24-year-old male without any other primary tumor. Total parotidectomy and neck dissection were performed followed by adjuvant chemoradiation. The patient remained alive and well 10 months after diagnosis. Histology showed keratinizing SCC infiltrating extensively the parotid gland with subtle poroid cell features. Oncogenic HPV infection was excluded by DNA-based testing. NGS analysis using the TruSight RNA fusion panel (Illumina) revealed a novel YAP1-MAML2 gene fusion. This gene fusion was reported recently in a subset of cutaneous porocarcinoma and poroma. This case of poroid SCC (or squamoid porocarcinoma) adds to the differential diagnosis of SCC presenting as parotid gland tumor and highlights the value of molecular testing in cases with unusual presentation.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Head and neck; MAML2; Parotid; Porocarcinoma; Poroma; Salivary glands; Squamous cell carcinoma; YAP1

YAP1-NUTM1 Gene Fusion in Porocarcinoma of the External Auditory Canal - Agaimy, Abbas; Tögel, Lars; Haller, Florian; Zenk, Johannes; Hornung, Joachim; Märkl, Bruno (Head and Neck Pathology, 2020)
Gene fusions involving the NUTM1 gene (NUT) represent defining genetic markers of a highly aggressive carcinoma type with predilection for the midline structures of children and young adults, hence the original description as NUT midline carcinoma. Recent studies have increasingly documented involvement of the NUTM1 gene in the pathogenesis of other entities as well. We herein describe two cases of auditory canal carcinomas with features of porocarcinoma, both harboring a newly described YAP1-NUTM1 gene fusion. Patients were males aged 28 and 82 years who presented with slowly growing lesions in the external auditory canal. Histologic examination showed monomorphic basaloid and squamoid cells arranged into organoid solid aggregates, nests, ducts, small cysts, and focal pseudocribriform pattern with variable mitotic activity, infiltrative growth, and focal squamous differentiation, particularly in the most superficial part of the tumor. Immunohistochemistry revealed consistent reactivity for CK5, p63 and SOX10 and diffuse aberrant expression of TP53. CK7 expression was limited to a few luminal ductal cells. The androgen receptor and S100 were negative. Next generation sequencing (TruSight RNA fusion panel, Illumina) revealed the same YAP1-NUTM1 gene fusion in both tumors, which was subsequently confirmed by NUT-FISH and the monoclonal anti-NUT antibody. These cases represent a novel contribution to the spectrum of NUT-rearranged head and neck malignancies. This adnexal carcinoma variant should not be confused with the highly lethal NUT carcinoma based on NUT immunoreactivity alone.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Auditory canal; Ear; Head and neck; Midline carcinoma; NUT carcinoma; NUTM1; YAP1